ANALYSING TEXTBOOKS WRITTEN BASED ON CURRICULUM 2006 AND CURRICULUM 2013 - Lilis Patria; Sudarsono Sudarsono; Yohanes Gatot Sutapa Yuliana; Ikhsanudin Ikhsanudin (Journal of English Educational Study (JEES), 2023)
Education is part of human life. It is given to individuals differently according to where the educational activities occur. In order to maintain the consistency of education in specific areas, there is a need for a curriculum to define how the materials and learning standards must be taught and achieved in educational institutes based on the customs of every area across the world. One curriculum implementation method is textbooks. They are tools where curriculum materials and standards are implemented to support teaching and learning activities. Textbooks always need help with the contents related to the implemented curriculum. There is a need for evaluation to assess the effectiveness and efficiency of textbooks. This study examines the existing implemented curriculum with the textbook contents. Two textbooks, "Bahasa Inggris" based on the Indonesian 2013 curriculum and "Developing English Competences" based on the Indonesian KTSP 2006 curriculum, are used for assessment and evaluation. The qualitative method called document analysis implements McGrath's theory to evaluate textbooks. The findings are the difference and validity between the textbooks contents and both the curriculum of 2013 and 2006 (KTSP). Both are considered suitable, but with some difficulties in teaching and learning activities at certain degrees.